Pre-registered Nursing students beliefs, attitudes and perceived knowledge of Hepatitis C and standard universal precautions - Calape, Divina (2011)
Hepatitis C is a growing health issue. With no cure or vaccine in sight, and the burden and cost of the disease proving expensive to both the National Health Service and the patient, its increase in incidence is worth noting, especially since the implementation of universal precautions can help reduce the spread of infection. Yet many studies have documented a lack of basic knowledge and understanding with regards to the disease or compliance with infection control, amongst registered health professionals. This can have negative effects on patient as care, and lead to discriminatory practice. As a result, the aim of this study is to explore pre-registration nursing students perceived knowledge, attitudes and beliefs surrounding Hepatitis C and universal precautions. A qualitative approach was adopted, and eight semi-structured interviews were performed on pre-registration nurses on the masters and Diploma/Degree programme. Interviews were transcribed, coded and interpreted using thematic analysis. The four themes of General knowledge and understanding of hepatitis C and universal precautions, Education and experience, the nurse’s role in hepatitis C management and Health Promotion, were identified.